(untitled) (Marketing Journal, 2025)
Modern information technologies play a crucial role in the rapid development of the digital economy, significantly impacting economic growth. This study analyzes the influence of ICT, the internet, artificial intelligence, and e -commerce on economic develo pment, both globally and within Uzbekistan. Comparative and statistical analyses confirm the contribution of information technologies to labor productivity and GDP growth. The study concludes with practical recommendations to accelerate digital transformat ion processes.